The “Fortilat” Randomized Clinical Trial Follow-Up: Auxological Outcome at 18 Months of Age - Peila, Chiara (Nutrients, 2020)
Human milk fortification is a routine clinical practice for feeding preterm infants. We hypothesized that donkey milk can be a suitable basis for developing an innovative human milk fortifier. Our randomized controlled single-blind clinical trial, named “Fortilat”, evaluated the feeding tolerance, growth and clinical short-term outcomes in a population of preterm infants fed with a novel multi-component fortifier and a protein concentrate derived from donkey milk. The aim of the current study is to extend the previous findings and to evaluate the auxological outcomes of the infants enrolled in the “Fortilat” trial at 18 months of age. In the previous trial “Fortilat”, the fortification protocol followed was the same for the two groups, and the two diets were designed to be isoproteic and isocaloric. All infants enrolled in the trial were included in a premature infant developmental evaluation program consisting of hospital visits at 40 ± 1 weeks of postmenstrual age, and at 6, 12 and 18 months of corrected age. Weight, head circumference and length were expressed in z-score using neonatal Intergrowth21st and INeS charts at birth, and WHO 0–5 years growth charts at 18 months. 122 children (Bovine-arm = 62, Donkey-arm = 60) were included in this study. All the observations were recorded in the interval of 18 ± 3 months of the correct age. The two groups did not differ for head circumference, length or weight at 18 months of age. Our data show that fortifiers derived from donkey milk had not different long term auxological outcomes of standard bovine-derived fortifier, but the new donkey milk fortifier was well tolerated in our population.